Encyclopedia of meat sciences. - Dikeman, M. (Academic Press, 2024)
Encyclopedia of Meat Sciences, Third Edition, Three Volume Set is the most up-to-date reference work on topics central to agricultural and food science researchers at all levels. With over 250 outstanding articles written by world leading experts, the book offers unparalleled coverage of the science and technology of producing and harvesting animals for meat, along with tactics for preservation and processing. Clearly divided into 12 distinct sections, topics covered include all aspects of the production of animals, poultry, fish and other species commonly 'farmed' and/or 'harvested', as well as the science of meat preservation and processing and consumer issues. New to this third edition are chapters covering the core scientific advancements of recent years, including gene editing of animals, sustainability and zoonotic diseases. In addition, the book introduces a templatized chapter approach, thus providing consistency to the entire work and maximizing the clarity and accessibility of its content for the reader. Chapters, once again, include a variety of images, charts, graphs, and/or diagrams to enhance the text.